Clinical outcomes of percutaneous coronary intervention for de novo lesions in small coronary arteries: A systematic review and network meta-analysis - Ma, Wen-Rui; Chandrasekharan, Karthik H.; Nai, Chang-Sheng; Zhu, Yong-Xiang; Iqbal, Javaid; Chang, Shang; Cheng, You-Wei; Wang, Xin-Yu; Bourantas, Christos V.; Zhang, Yao-Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: Percutaneous coronary intervention (PCI) has a well-established role in revascularization for coronary artery disease. We performed network meta-analysis to provide evidence on optimal intervention strategies for de novo lesions in small coronary arteries. Methods: Enrolled studies were randomized clinical trials that compared different intervention strategies [balloon angioplasty (BA), biolimus-coated balloon (BCB), bare-metal stent (BMS), new-generation drug-eluting stent (New-DES), older generation sirolimus-eluting stent (Old-SES), paclitaxel-coated balloon (PCB), and paclitaxel-eluting stent (PES)] for de novo lesions in small coronary arteries. The primary outcome was major adverse cardiac events (MACE). Results: A total of 23 randomized clinical trials comparing 7 intervention devices were analyzed. In terms of the primary outcome, New-DES was the intervention device with the best efficacy (surface under the cumulative ranking curve (SUCRA), 89.1%; mean rank, 1.7), and the Old-SES (RR, 1.09; 95%CI, 0.45-2.64) and PCB (RR, 1.40; 95%CI, 0.72-2.74) secondary to New-DES, but there was no statistically significant difference between these 3 intervention devices. All DES and PCB were superior to BMS and BA for MACE in both primary and sensitivity analysis. For secondary outcomes, there was no association between all-cause mortality and myocardial infarction (MI) with any intervention strategy, and additionally, the findings of target lesion revascularization (TLR) were similar to the primary outcomes. Conclusions: PCB yielded similar outcomes to New-DES for de novo lesions in small coronary arteries. Therefore, this network meta-analysis may provide potential support for PCB as a feasible, effective, and safe alternative intervention strategy for the revascularization of small coronary arteries.